2020
DOI: 10.1021/acs.jmedchem.9b01990
|View full text |Cite
|
Sign up to set email alerts
|

Twelfth-Position Deuteration of Nevirapine Reduces 12-Hydroxy-Nevirapine Formation and Nevirapine-Induced Hepatocyte Death

Abstract: Cytochrome P450-dependent metabolism of the anti-HIV drug nevirapine (NVP) to 12-hydroxy-NVP (12-OHNVP) has been implicated in NVP toxicities. We investigated the impact of twelfth-position trideuteration (12-D 3 NVP) on the hepatic metabolism of and response to NVP. Formation of 12-OHNVP decreased in human (10.6-fold) and mouse (4.6-fold) hepatocytes incubated with 10 μM 12-D 3 NVP vs NVP. An observed kinetic isotope effect of 10.1 was measured in human liver micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…The same group also reported data obtained from a proteomics study performed with HepG2 cells cultured for one week with 819 μM NVP, in which nearly 40% of the differentially expressed proteins were mitochondrial proteins, providing evidence of NVP interfering with mitochondria in this model [ 77 ]. Conversely, we have shown that NVP lacks mitochondrial toxicity in another human hepatoma cell line, Hep3B, though the treatment in question (10–50 µM) lasted only a few hours [ 78 ]. Differences in the expression of drug-metabolizing genes between HepG2 and Hep3B cells may explain this discrepancy.…”
Section: Mechanisms Of Nnrti-induced Liver Injurymentioning
confidence: 99%
“…The same group also reported data obtained from a proteomics study performed with HepG2 cells cultured for one week with 819 μM NVP, in which nearly 40% of the differentially expressed proteins were mitochondrial proteins, providing evidence of NVP interfering with mitochondria in this model [ 77 ]. Conversely, we have shown that NVP lacks mitochondrial toxicity in another human hepatoma cell line, Hep3B, though the treatment in question (10–50 µM) lasted only a few hours [ 78 ]. Differences in the expression of drug-metabolizing genes between HepG2 and Hep3B cells may explain this discrepancy.…”
Section: Mechanisms Of Nnrti-induced Liver Injurymentioning
confidence: 99%
“…NVP is metabolized by cytochrome P450, resulting in the formation of four mono-oxygenated metabolites, of which 12-hydroxy-NVP (12-OHNVP) is associated with hepatotoxicity and skin toxicity [78,79]. In a recent study using primary mouse hepatocytes, supra-therapeutic concentrations of NVP-induced cell death, while a version of the drug in which the twelfth-position had been trideuterated (12-D3NVP) exerted a lesser effect in comparison to NVP [80]. In contrast, in another study assessing the toxicity of two-day exposure of primary hepatocytes from five human donors to NVP or ritonavir (RTV), the former inhibited EIF2 signaling and was predicted to suppress downstream ATF4and CHOP-related apoptotic pathways (revealed by analysis of transcriptomic data) and PDI and heat shock responses.…”
Section: Nnrtismentioning
confidence: 99%
“…Primarily, CYP2B6 and CYP3A4 metabolize NVP to 2-hydroxynevirapine (OH-NVP), 3-OH-NVP, 8-OH-NVP, and 12-OH-NVP. However, reactive metabolite, 12-sulphoxynevirapine (12-SUL-NVP) from the SULTs biotransformation of 12-OH-NVP is also known to be a major cause of NVP Hypersensitivity (20,21). Highly polymorphic sulfotransferase 1A1 (SULT1A1), is marked with differences in their variants (1A1*1, 1A1*2 and 1A1*3) with signi cantly reduced enzyme activity (22).…”
Section: Introductionmentioning
confidence: 99%